All-inorganic perovskite quantum dot light-emitting memories - Yen, Meng-Cheng; Lee, Chia-Jung; Liu, Kang-Hsiang; Peng, Yi; Leng, Junfu; Chang, Tzu-Hsuan; Chang, Chun-Chieh; Tamada, Kaoru; Lee, Ya-Ju (Nature communications, 2021)
Field-induced ionic motions in all-inorganic CsPbBr 3 perovskite quantum dots (QDs) strongly dictate not only their electro-optical characteristics but also the ultimate optoelectronic device performance. Here, we show that the functionality of a single Ag/CsPbBr 3 /ITO device can be actively switched on a sub-millisecond scale from a resistive random-access memory (RRAM) to a light-emitting electrochemical cell (LEC), or vice versa, by simply modulating its bias polarity. We then realize for the first time a fast, all-perovskite light-emitting memory (LEM) operating at 5 kHz by pairing such two identical devices in series, in which one functions as an RRAM to electrically read the encoded data while the other simultaneously as an LEC for a parallel, non-contact optical reading. We further show that the digital status of the LEM can be perceived in real time from its emission color. Our work opens up a completely new horizon for more advanced all-inorganic perovskite optoelectronic technologies. Electric field induced ion migration is a well-known phenomenon in perovskite, but the consequences are notorious, and thus needs to be prevented. Here, on the other hand, the authors cleverly manipulate this event for realising resistive random-access memory and light-emitting electrochemical cell in one device based on CsPbBr 3 quantum dots.